The Present Status and Prospect of Research on Rapid Freeze-drying Food in China - Li, Hua; Jiao, Xingli; Geng, Longgang (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The basic principles, process, features, technology advances, mechanistic modelling of the phenomena involved and present status of freeze-dried food were introduced in this paper, in which the main problems of the freeze-dried food in our country were proposed, and its main development trend was also analyzed.